SANITARY EVALUATION OF MILK PRODUCTS IN MOUNTAIN DAIRIES - R. Mioni; A. Paiusco; L. Ravella; D. Comin (Italian Journal of Food Safety, 2010)
between 2006 and 2007 881 samples of “malga” (little mountain dairies) milk products were analysed to estimate their hygienic characteristics. Several samples showed high counts for Escherichia coli and coagulase-positive staphylococci, while Salmonella spp. and Campylobacter spp. were absent in all of the samples; 0,9% of cheese samples, 4,1% of butter samples and 4,7% of “ricotta” samples were positive for Listeria monocytogenes, so as 14,7% of cheese samples for staphylococcal enterotoxins.